2019
DOI: 10.1021/acsami.8b19055
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle Probe-Assisted Antigen-Counting Chip Using SEM

Abstract: Currently, it remains challenging to count protein-biomarker molecules present in a small droplet of biological samples. Herein, we propose a gold nanoparticle (GNP) probe-assisted sandwich-counting strategy that relies on a GNP probe, an antibody-functionalized chip to “count” antigen molecules using a scanning electron microscope. Both standard carcinoembryonic antigen (CEA) and two real CEA-related tumor samples (tumor tissues and serum) were assayed to demonstrate the proof-of-concept of the counting strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The detection limit was as low as 7.6 pg mL −1 (3 σ/K , where σ stands for the standard deviation of 10 blank controls, K stands for the slope of regression equation). The analytical performances of other CEA assays [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ] were listed in Table S1 and compared with our designed ELISA method. The results showed that the sensitivity of this FLISA method was comparable or even better than other analytical methods.…”
Section: Resultsmentioning
confidence: 99%
“…The detection limit was as low as 7.6 pg mL −1 (3 σ/K , where σ stands for the standard deviation of 10 blank controls, K stands for the slope of regression equation). The analytical performances of other CEA assays [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ] were listed in Table S1 and compared with our designed ELISA method. The results showed that the sensitivity of this FLISA method was comparable or even better than other analytical methods.…”
Section: Resultsmentioning
confidence: 99%
“…Third, most of the current protein microarray results are difficult to quantify accurately. To achieve accurate quantification, which is key to most systems biology research, some researchers have attempted to improve the protein microarray quantitation methods, such as the gold nanoparticle (GNP) probe-assisted sandwich-counting strategy proposed by Zhou et al [108].…”
Section: Perspectivesmentioning
confidence: 99%
“…Plasmonic metal nanoparticle (MNP) based assays have been applied to detecting multiple species of analytes from smallest molecules to large cells through a variety of signal transduction mechanisms, e.g., surface plasmon resonance, surface enhance Raman spectra, AuNP enhanced fluorescent, colorimetry, scanning electron microscope (SEM) and so on [24][25][26][27][28] . Here in our Nano2RED assay design, AuNPs are conjugated with synthesized nanobodies to form multivalent sensors that aggregate at the presence of specific antigen and subsequently precipitate, thus producing antigen-concentration-dependent signals that can be generated within minutes and 7 readily quantified by optical and electronic readout.…”
Section: Nanobody-conjugated Nanoparticles For Rapid Electronic Detection (Nano2red)mentioning
confidence: 99%